Vicende dell’etica: storia, concetti, contaminazioni - Fonnesu, Luca (Filosofia Morale/Moral Philosophy, 2022)
In the attempt to offer a helpful answer to the question about the future of moral philosophy, this essay sheds light on three key aspects of the current ethical research. For starters, the relevance of the history of ethics within a theoretical framework widely dominated by the analytic tradition. Secondly, the central role that the notion of responsibility has gained in the contemporary analysis of moral concepts. Finally, the innovative relationship between ethics and epistemology, which speaks of the growing influence of other disciplines within the ethical discussion. As will become clear, the essay devotes special attention to the discussions and research lines that demonstrate how philosophers in Italy are contributing to the current debate in moral philosophy.